OPTIMIZING SHARIA INVESTMENT PORTFOLIOS USING MODERN PORTFOLIO THEORY: A CASE STUDY OF ICBP AND SIDO IN INDONESIA STOCK MARKET - Rinaima, Chetrine Alya; Fauziyah, Nur; Kamilah, Athia Nur (Airlangga International Journal of Islamic Economics and Finance, 2025)
This study evaluates the benefits of portfolio diversification by examining the relationship between the returns of Sido Muncul Tbk (SIDO) and Indofood CBP Sukses Makmur Tbk (ICBP) using Modern Portfolio Theory (MPT). Daily closing prices from October 1, 2023, to September 30, 2024, were analyzed. Daily returns were calculated and assessed using descriptive statistics, Pearson correlation, and mean–variance optimization to construct the efficient frontier and identify the optimal allocation. The results show ICBP offers a lower return (6.25%) and lower risk (1.92), while SIDO provides a higher return (7.35%) with slightly higher risk (1.97). Portfolio optimization suggests a 50/50 allocation yields the most balanced outcome, minimizing risk (1.46) while maintaining a solid return (6.80%). The low correlation (0.13) between the two stocks highlights significant diversification benefits. Practical implications include providing Shariah-compliant investors with empirical guidance to build efficient portfolios that balance return and risk. The study is limited by its use of only two stocks and a one-year observation period, which may affect the generalizability of results to broader market conditions. Keywords: Modern Portfolio Theory, Portfolio Optimization, Efficient Frontier, Islamic Investment, Investment Decision-Making